Mycorrhizal-Assisted Phytoremediation and Intercropping Strategies Improved the Health of Contaminated Soil in a Peri-Urban Area - Gómez-Sagasti, María Teresa; Garbisu, Carlos; Urra, Julen; Míguez, Fátima; Artetxe, Unai; Hernández, Antonio; Vilela, Juan; Alkorta, Itziar; Becerril, José M. (Frontiers in Plant Science, 2021)
Soils of abandoned and vacant lands in the periphery of cities are frequently subjected to illegal dumping and can undergo degradation processes such as depletion of organic matter and nutrients, reduced biodiversity, and the presence of contaminants, which may exert an intense abiotic stress on biological communities. Mycorrhizal-assisted phytoremediation and intercropping strategies are highly suitable options for remediation of these sites. A two-year field experiment was conducted at a peri-urban site contaminated with petroleum hydrocarbons and polychlorinated biphenyls, to assess the effects of plant growth (spontaneous plant species, Medicago sativa, and Populus × canadensis, alone vs. intercropped) and inoculation of a commercial arbuscular mycorrhizal and ectomycorrhizal inoculum. Contaminant degradation, plant performance, and biodiversity, as well as a variety of microbial indicators of soil health (microbial biomass, activity, and diversity parameters) were determined. The rhizosphere bacterial and fungal microbiomes were assessed by measuring the structural diversity and composition via amplicon sequencing. Establishment of spontaneous vegetation led to greater plant and soil microbial diversity. Intercropping enhanced the activity of soil enzymes involved in nutrient cycling. The mycorrhizal treatment was a key contributor to the establishment of intercropping with poplar and alfalfa. Inoculated and poplar-alfalfa intercropped soils had a higher microbial abundance than soils colonized by spontaneous vegetation. Our study provided evidence of the potential of mycorrhizal-assisted phytoremediation and intercropping strategies to improve soil health in degraded peri-urban areas.